Game Theory and Peace Research: Professor Anatol Rapoport’s Contributions (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
At the forefront of the game theoreticians who conceived of concepts that contributed to peace research and conceptualized strategies that could promote international cooperation, Professor Anatol Rapoport used simple game theory in the classroom to generate ideas about how to enhance world peace. The basic logic of game theory is explained using his game models of ‘Chicken’ and ‘Prisoner’s Dilemma’. Rapoport’s revolutionary ideas about how to promote international and national cooperation are overviewed; for instance he developed a simple strategy, Tit for Tat, to help minimize conflict that won two computer tournaments, and he taught scholars to consider the risks of nuclear deterrence. He was one of North America’s pre-eminent peace researchers and his legacy will live on for generations of future scholars and policy makers.
Keywords: chicken game; cooperation; game theory; peace research; prisoner’s dilemma; Rapoport